2019
DOI: 10.1177/0022146519849027
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Conceptualizations of Responsibility for Healthcare: A Typology for Understanding Differing Attributions in the Context of Patient Safety

Abstract: This study examines how patients conceptualize 'responsibility' for their healthcare and make sense of the complex boundaries between patient and professional roles. Focusing on the specific case of patient safety, narrative methods were used to analyze semi-structured interviews with 28 people recently discharged from hospital in England. We present a typology of attribution, which demonstrates that patients' attributions of responsibility to staff and/or to patients are informed by two dimensions of responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 53 publications
3
34
0
9
Order By: Relevance
“…However, staff within this study did not appear to engage in quality improvement activities based on patient experiences of safety, and we are therefore only able to conclude that patient feedback on their safety could lead to quality improvement, but that other individual, structural, procedural and cultural conditions are required to be met first. This supports existing research that patients should be involved in the improvement process, providing their involvement is managed correctly [41, 42] and they welcome having some responsibility for their safety [43]. For instance in one study [44] using a national patient survey for quality improvement, it was identified that staff were largely receptive to the survey results but that there were a number of barriers.…”
Section: Discussionsupporting
confidence: 67%
“…However, staff within this study did not appear to engage in quality improvement activities based on patient experiences of safety, and we are therefore only able to conclude that patient feedback on their safety could lead to quality improvement, but that other individual, structural, procedural and cultural conditions are required to be met first. This supports existing research that patients should be involved in the improvement process, providing their involvement is managed correctly [41, 42] and they welcome having some responsibility for their safety [43]. For instance in one study [44] using a national patient survey for quality improvement, it was identified that staff were largely receptive to the survey results but that there were a number of barriers.…”
Section: Discussionsupporting
confidence: 67%
“…Discharge was seen by many in the hospital as the end point of responsibility, whilst in the community the diffuse nature of care provision meant that no one took responsibility (Heavey et al . ).
I think there just somehow seems to be a void between hospital and community where things sort of fall down. Almost like a bit of a hurdle.
…”
Section: Resultsmentioning
confidence: 97%
“…The dilemmas of ‘knowing’ the person and determining ‘eligibility’ set the parameters for establishing professional ‘non‐responsibility’ for care; that is, the inability to define an eligible subject makes the responsibility for care diffuse (Heavey et al . ). This is similar to the ‘problem of many hands’ where the distribution of responsibility amongst multiple actors can mean that no one professional ultimately takes responsibility (Dixon‐Woods and Pronovost ).…”
Section: Discussionmentioning
confidence: 97%
“…As for study design, it was observed that most of the articles (37.9%) used mixed methods 15,16,17,18,19,20,21,22,23,24,25 and the same proportion (31%) adopted qualitative 26,27,28,29,30,31,32,33,34 and quantitative approaches 19,35,36,37,38,39,40,41 . There was variation in sample size and type according to quantitative and/or qualitative design.…”
Section: Resultsmentioning
confidence: 99%